2008
DOI: 10.1002/mnfr.200700240
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide in home‐prepared roasted potatoes

Abstract: Potato is one of the world's most widely grown tuber crop, in which starch is the predominant form of carbohydrates. Potatoes can be prepared in many ways: boiled, fried or roasted. Frying and roasting potatoes at high temperatures result in an appetizing crust, but at the same time acrylamide can form. In this study, the concentrations of the acrylamide precursors, asparagine and sugars, were determined in five different Swedish-grown potato varieties, together with the acrylamide content after typical home-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Asparagine content may be the limiting factor for acrylamide synthesis when the molar ratio of reducing sugars to asparagine content is more than two, indicating an abundance of reducing sugars (Matsuura-Endo et al, 2006). In contrast, a different study found no link between the presence of precursors (asparagine and sugars) and the production of acrylamide (Skog et al, 2008). The necessity to research the concentration of asparagine in connection to various aspects, such as production parameters and maturity stage, is driven by the fact that asparagine is the limiting element for the creation of acrylamide in plantain chips (Kansci et al, 2016).…”
Section: Vi) Storage Conditions and Glucose/fructose Rationmentioning
confidence: 95%
“…Asparagine content may be the limiting factor for acrylamide synthesis when the molar ratio of reducing sugars to asparagine content is more than two, indicating an abundance of reducing sugars (Matsuura-Endo et al, 2006). In contrast, a different study found no link between the presence of precursors (asparagine and sugars) and the production of acrylamide (Skog et al, 2008). The necessity to research the concentration of asparagine in connection to various aspects, such as production parameters and maturity stage, is driven by the fact that asparagine is the limiting element for the creation of acrylamide in plantain chips (Kansci et al, 2016).…”
Section: Vi) Storage Conditions and Glucose/fructose Rationmentioning
confidence: 95%
“…After cooling (15 min at À201C), 10 mL of internal standard solution (1 mg/mL of labeled [1,2,[3][4][5][6][7][8][9][10][11][12][13] C 3 ]acrylamide in methanol) and 2 mL of 0.3 M sodium citrate buffer, pH 2.2, were added. Suspensions were stirred for 1 min, the supernatant was then filtered and its acrylamide content determined.…”
Section: Carbonyl-amine Reactionsmentioning
confidence: 99%
“…137 In general, the acrylamide content in the final potato products should be closely related to the contents of asparagine and sugars. However, Skog et al 138 indicated that no correlation was found between precursor contents and acrylamide content in home-prepared roasted potatoes. This finding may emphasize the need for further studies on factors affecting acrylamide formation, for example, the availability of precursors at the surface during cooking.…”
Section: Potatoesmentioning
confidence: 99%